2017
DOI: 10.1016/j.jaac.2017.09.428
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Stress Interacts With Bipolar Disorder Genetic Risk to Increase Risk for Suicide Attempts

Abstract: Objective Bipolar disorder (BD) is one of the most heritable psychiatric conditions and is associated with high suicide risk. To explore the reasons for this link, this study examined the interaction between traumatic stress and BD polygenic risk score in relation to suicidal ideation, suicide attempt, and nonsuicidal self-injury (NSSI) in adolescent and young adult offspring and relatives of persons with BD (BD-relatives) compared with adolescent and young adult offspring of individuals without psychiatric di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 49 publications
2
29
0
Order By: Relevance
“…Prior to imputation using the Michigan Imputation Server (v1.0.3), 17 genotypes of 1333 participants underwent pre‐imputation QC following the ENIGMA2 protocols (Phase 3, version 5), and were combined after pre‐imputation QC with 1472 other Caucasian cohort samples, also genotyped on PsychArray at Mt Sinai, 18 to maximize the sample and improve imputation accuracy. Details of pre‐imputation quality control, identity‐by‐descent and principal component analysis (PCA) and imputation details are provided in Supplementary Online Material.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to imputation using the Michigan Imputation Server (v1.0.3), 17 genotypes of 1333 participants underwent pre‐imputation QC following the ENIGMA2 protocols (Phase 3, version 5), and were combined after pre‐imputation QC with 1472 other Caucasian cohort samples, also genotyped on PsychArray at Mt Sinai, 18 to maximize the sample and improve imputation accuracy. Details of pre‐imputation quality control, identity‐by‐descent and principal component analysis (PCA) and imputation details are provided in Supplementary Online Material.…”
Section: Methodsmentioning
confidence: 99%
“…A PS for schizophrenia predicted SSH among offspring of suicide attempters [25] and in a population sample [27], but not in another clinical sample [28]. A PS for bipolar disorder predicted SSH in 1 clinical sample [29] but did not predict SSH nor NSSH among offspring of suicide attempters [25] or relatives of PLOS MEDICINE bipolar disorder patients [30]. A recently published study showed that PSs for cannabis use and MDD predicted self-harm in the UK Biobank sample [31].…”
Section: Introductionmentioning
confidence: 92%
“…17 Finally, the interaction between BD polygenic risk score and childhood maltreatment was significantly associated with suicide attempts in a sample of relatives of patients with BD and healthy controls. 18 To date, no investigations of the interactions between BD-PRS and childhood maltreatment on the clinical expression of BD has been published and further explorations are thus warranted.…”
Section: Introductionmentioning
confidence: 99%